Nicolau syndrome following intramatricial triamcinolone injection for nail lichen planus - Chander Grover (Indian Dermatology Online Journal, 2017)
Nicolau syndrome (Embolia cutis medicamentosa) is a rare complication following parenteral administration of a drug. It has been reported in association with intramuscular, subcutaneous, intravenous and intra-articular injections. However, Nicolau syndrome following intramatricial injection has not been described to the best of our knowledge. We report the case of an 18-year-old male who developed this complication following 7th session of intramatricial injection. The patient was started on broad spectrum antibiotic coverage, vasodilator therapy, analgesics, and daily dressing. On day 21, the symptoms completely resolved with return of normal color of the digit. The case is being reported to make dermatologists aware of the possibility of Nicolau syndrome following intramatricial injection of triamcinolone acetonide.